PENGEMBANGAN MODUL PEMBELAJARAN KIMIA BERBASIS SETS PADA MATERI HIDROLISIS GARAM UNTUK SISWA SMA - Nggua Li, Maria Yersiana; Hairida, Hairida; Rasmawan, Rahmat (EduChem, 2023)
The aims of this research were to determine the feasibility of the SETS-Based Learning Module (Science, Environment, Technology, And Society) which was developed based on the results of expert judgment and student responses based on the results of the readability test. The form of this research is research and development (RD) which adopts the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subject of this research is SETS (Science, Environment, Technology, And Society) Based Learning Module which was tested on 9 students of SMA Kristen Abdi Wacana in the initial readability test and 24 students in SMA Kristen Abdi Wacana Pontianak in the main reading test. The data collection instruments used were the feasibility assessment sheet and the student questionnaire responses. The results of data processing show that the learning module developed is suitable for use in learning in terms of the feasibility of the material with a validity value of 0.99, the value of language validity and graphic 1. Based on the results of the calculation of the percentage of student questionnaire responses, the initial trial results of 88.24% and in the field trials of 87.8%. This shows that the response of students to the SETS-Based Learning Module (Science, Environment, Technology, And Society) is classified as very high category. Keywords:Learning Module, SETS (Science, Environment, Technology, And Society), Salt Hydrolysis